Pengaruh Pengangguran, Kemiskinan, serta Indeks Pembangunan Manusia (IPM) terhadap Kesenjangan Pendapatan di Kabupaten atau Kota Provinsi Banten Periode Tahun 2019-2023 - Salsabila, Alya; Azaria, Naura Sultania; Ramdhani, Novita; Amanda, Amanda; Christina, Angelicha (Neolectura, 2024)
This study aims to analyze the impact of unemployment, poverty, and the Human Development Index (HDI) on income inequality in the regencies and cities of Banten Province during the period 2019-2023. This research uses secondary data obtained from the Central Bureau of Statistics (BPS). The population in this study includes all regencies and cities in Banten Province, with the sample being time series data from 8 regencies/cities over five years. The research method used is panel data regression with the STATA 14 application. The research instrument includes independent variables such as unemployment, poverty, and HDI, and the dependent variable is income inequality measured by the Gini ratio. The results show that unemployment and HDI have a significant influence on income inequality, while poverty does not have a significant effect. Increases in unemployment and HDI tend to increase income inequality. Additionally, the study found that improvements in HDI, including enhancements in educational and health infrastructure, contribute to the increase in income inequality. These findings have important implications for economic policies to reduce income inequality in Banten Province.